2012
DOI: 10.1590/s1984-29612012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii antibodies sheep in Lages, Santa Catarina, Brazil, and comparison using IFA and ELISA

Abstract: Toxoplasmosis in sheep is a disease of great importance in veterinary medicine, which causes economic losses in livestock and has a great impact on human health, since consumption of infected meat facilitates transmission of zoonotic infections. Blood samples from sheep (n = 360) were collected from 13 farm properties in the municipality of Lages, Santa Catarina, to estimate the prevalence of toxoplasmosis and identify risk factors associated with Toxoplasma gondii infection. T. gondii, antibodies were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…These data are consistent with Mendonça et al, (2013), Pereira et al, (2012); Sakata et al (2012), who found no relationship between age and seroprevalence to increase toxoplasmosis. Sakata et al (2012) suggest changes in the incidence of toxoplasmosis depending on the breed of the animal and explain that this fact may be related to the management of the animals. However, in this work no significant difference was found for the breeds analyzed Table 8 when compared through the result of IFAT and ELISA, table 2.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These data are consistent with Mendonça et al, (2013), Pereira et al, (2012); Sakata et al (2012), who found no relationship between age and seroprevalence to increase toxoplasmosis. Sakata et al (2012) suggest changes in the incidence of toxoplasmosis depending on the breed of the animal and explain that this fact may be related to the management of the animals. However, in this work no significant difference was found for the breeds analyzed Table 8 when compared through the result of IFAT and ELISA, table 2.…”
Section: Resultssupporting
confidence: 91%
“…The seroprevalence was obtained through IFAT for the IZ sheep herd of 21.51%, according to table 4. Results varied for the literature for the different forms of the Brazilian states, through IFAT, varying from 7% in Paraná (MOURA et al, 2007) and 80% in Santa Catarina (SAKATA et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Sakata et al (2012) found a seroprevalence of 56.94% among sheep in the municipality of Lages, State of Santa Catarina. This high prevalence, in comparison to that obtained in the present study, may be explained by the high humidity of the Lajes region, with greater and more regular rainfall, which may contribute towards higher viability among T. gondii oocysts in the environment.…”
Section: Resultsmentioning
confidence: 93%
“…The number of sheep to be sampledin each flock was determined individually per flock using the formula for detecting the presence of infection (THRUSFIELD, 2007). The probability of detecting at least one seropositive animal in the flock was determined with a 95% confidence level (P = 0.95) and the number of seropositive animals per flock was calculated assuming an intra-flock prevalence of 56.94% (SAKATA et al, 2012). In total, 540 animals from 63 flocks in 14 municipalities in the Sertão mesoregion were used.…”
Section: Samplingmentioning
confidence: 99%
“…The frequency of infection is extremely high in other regions of Brazil. In Santa Catarina, Sakata et al (2012) detected an occurrence of 56.9%. Ferreira et al (2016) reported an occurrence of 41.3% in sheep from Rio Grande do Sul.…”
Section: Resultsmentioning
confidence: 94%